Electricity and magnetism (United Kingdom : Anglia Multimedia, 2000)
Since the early experiments with the electricity over two hundred years ago, scientists have made many discoveries which help explain its nature. These discoveries have linked many areas of science including static electricity, electric current, magnetism and materias. In all areas of our life, at home and at school, we rely on electricity, which has become a crucial part of modern society. Electricity and magnetism has a highly interactive design where the user plays an active part in the learning process rather than being a passive observer.
Education version.
System requirements: IBM compatible minimum 486DX2/66MHz (Pentium recommended), 8Mb of RAM (16Mb recommended), Sound Blaster compatible sound card, Windows 95/98/NT; Macintosh or Powr Macintosh, System 7 or above (including System 8), 8Mb of RAM (16Mb recommended); requires mpouse and double speed 300 kps CD-ROM drive, VGA 256 colour, 640 x 480 display.
Keywords: Electricity; Magnetism